A comparative study of hot filling and ozonation for mango puree preservation - Macansantos,Tara Sarinandi L. (1998.)
Two processing methods were used for the preservation of mango puree namely, hot filling and ozonation.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Mango puree; Mango